2014
DOI: 10.1063/1.4864281
|View full text |Cite
|
Sign up to set email alerts
|

3 ns single-shot read-out in a quantum dot-based memory structure

Abstract: Articles you may be interested inSingle-and few-electron dynamic quantum dots in a perpendicular magnetic field J. Appl. Phys. 109, 102422 (2011); 10.1063/1.3578685 Effect of carriers transfer behavior on the optical properties of InAs quantum dots embedded in AlGaAs/GaAs heterojunction J. A write time of 6 ns for quantum dot-based memory structures Appl. Phys. Lett. 92, 092108 (2008); 10.1063/1.2890731Room-temperature operations of memory devices based on self-assembled InAs quantum dot structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our method is not limited to slow relaxations. In related experiments on quantum dots, sampling rates higher than 300 MHz have been obtained 24 . The basic principal behind the demonstrated method is very versatile and we suggest to perform this characterization measurements on different dielectric materials in the future and also with different two-dimensional carrier gases.…”
Section: Discussionmentioning
confidence: 99%
“…Our method is not limited to slow relaxations. In related experiments on quantum dots, sampling rates higher than 300 MHz have been obtained 24 . The basic principal behind the demonstrated method is very versatile and we suggest to perform this characterization measurements on different dielectric materials in the future and also with different two-dimensional carrier gases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the 2DEG is a very sensitive detector for time‐resolved measurements of the electron tunneling, the density of states, and charge state of the dots. For comparison, this measurement technique has many similarities with the read‐out process in a flash memory, .…”
Section: Electrical Transconductance Spectroscopymentioning
confidence: 99%
“…They behave with their zero-dimensional density of states like "artificial atoms" and are perfectly suited for fundamental studies on atom-like quantum states [1][2][3] in a solidstate environment. In contrast to "real atoms," the solid-state matrix enables electrical contacting; a situation that makes QDs highly interesting for future device applications, like QD-lasers [4][5][6], amplifiers [7][8][9], photodetectors [10,11], or memories [12][13][14]. More visionary applications want to use QDs as building blocks in quantum information processing [15][16][17].…”
mentioning
confidence: 99%
“…Limited studies have also examined the effect of the 2DEG on the optical properties of the SAQDs and shown that for barriers of 30 nm, ensemble emission spectra are largely unperturbed [50,51]. In addition, transport through the 2DEG has been used to detect charge occupation in the SAQD layer [52][53][54][55][56][57], and enable single photon detection by extension [58,59]. More recent investigations have started to explore the coupling between SAQDs and microcavity polaritons [60].…”
Section: Relation To Other Approaches In Quantum Coherent Semiconduct...mentioning
confidence: 99%